Microsoft front page 2000 complete concepts and techniques - Shelly, Gary B; Cashman, Thomas J; Mick, Michael L (Cambridge Thomsom Learning, 2000)
The Shelly Cashman Series: Frontpage 2000 book present material using a pedagogy that combines a project-oriented, step-by-step approach with corresponding screens and numerous exercises at the end of each project
Keywords: Web publishing; Web sites